EVALUATION OF CASES OF OBSTRUCTIVE JAUNDICE BY ULTRASOUND AND ERCP AT TERTIARY CARE TEACHING HOSPITAL - Saima Ikram; Nayab Alia; syed Hasan Akhtar Bokhari (Journal of University Medical & Dental College, 2015)
ABSTRACT: OBJECTIVES: To know causes of obstructive jaundice. To see co-relation of USG and ERCP ﬁndings. SETTINGS AND DURATION: This descriptive study was conducted at radiology department of Madinah Teaching Hospital and stGastroentrotology department of Madinah Teaching Hospital, Faisalabad from 1 November 2014 in patients coming from peripheral areas of Faisalabad. STUDY DESIGN: Descriptive study. PROJECT SUMMARY (200-250WORDS) OBJECTIVES: To determine the ﬁndings in ultrasound and ERCP in patients of obstructive jaundice. Obstructive jaundice (means when serum bilirubin level in greater than 50µmol/dL (3mg/dL). METHODOLOGY: Descriptive study was performed in Madinah Teaching Hospital to diagnose causes of obstructive jaundice. The study was performed by USG and ERCP in 55 patients having sign and symptoms of obstructive jaundice. RESULTS: Study shows that most of the patients having obstructive jaundice have mainly benign CBD causes and only 3 patients have malignant CBD causes. One patient has CA head of pancreas. Among these study cases 30 out of 55 have prolonged history of Cholelithiasis for 5-7years. 52/55 patients have same ﬁndings on USG and ERCP. So results are true positive in 52/55 patients.